Une fabrique publique d’entrepreneurs schumpétériens en France (1971-1978) - Jean-Baptiste Devaux (La Nouvelle Revue du Travail)
Policies to support innovation are now one of the main instruments for national governments to govern economy. They consist in giving companies or private and commercial operators primacy in the conduct of technological development. In the French case, these public policies appeared in the early 1970s and deeply transformed the tools by which the State governs science, technology and industry. This article proposes to bring to light the logics of action that structure these public policies from the analysis of the genesis of this public policy. We wish to show that this regime of "government by innovation" is first and foremost the product of competition between ministries and professional groups within the State for the control of this public policy. Through the work of senior civil servants, instruments of government are emerging by which the State aims to conform scientific, technical and industrial practices to the model of the Schumpeterian entrepreneur.